Does the presence of type II Diabetes affect cognitive decline in Alzheimer's Disease Dementia?. (20th December 2022) - Davidson, Skylar; Allenback, Gayle; Decourt, Boris; Sabbagh, Marwan N.
Abstract: Background: Alzheimer's disease (AD) is sometimes referred to as Type 3 diabetes. While it is very likely that insulin dysregulation and resistance participate in the etiology of AD pathologies, little is known about the possible correlation between diabetes and the progression of cognitive decline in AD patients. Previous studies have shown an increased risk of developing AD in patients with type 2 diabetes mellitus (T2DM). The specific aim of our study was to determine whether differences exist in cognitive decline experienced by AD subjects with and without T2DM co‐morbidity. Method: All cognitive performance data and the presence or absence of T2DM co‐morbidity in AD patients used in the present report were derived from the Uniform Data Set (UDS) of the database maintained by the National Alzheimer's Coordinating Center (NACC), USA. The scanning of the UDS database identified 3055 participants with AD who had more than one epoch completed. The dataset culled clinically‐diagnosed AD patients who were assessed for diabetes type in form A5 or D2 during at least one visit. These patients were divided into two groups dependent upon the presence of a diagnosis of T2DM. The data from these groups was then analyzed for differences in cognitive decline based upon Neuropsychological Battery Scores and a Clinician Dementia Rating (CDR) using a general linear model. Result: Cognitive function tests looked at language, cognitive executive function, and verbal and nonverbal memory. Comparison of the mean scores in 16 selected tests from the Neuropsychological Battery test showed no significant differences in baseline scores and scores at subsequent visits between the T2DM and non‐diabetic groups. Conclusion: Using the NACC database, which receives longitudinal data from Alzheimer's Disease research Centers (ADRCs), it was found that there were no differences in cognitive decline metrics over the course of 5 visits in either group. This supports the position that the presence of T2DM does not appear to increase the magnitude of cognitive decline in AD patients